Adlay starch-gluten composite gel: Effects of adlay starch on rheological and structural properties of gluten gel to molecular and physico-chemical characteristics. (15th August 2019) - Li, Changfeng; Chen, Guangjing; Ran, ChunXia; Liu, Linjing; Wang, Shasha; Xu, Yao; Tan, Yue; Kan, Jianquan
Highlights: Effects of adlay starch on the changes in wheat gluten gels were investigated. The viscoelastic behavior of gluten gel was improved by adding adlay starch. Adlay starch increased the free thiol content and β-sheet structure of gluten gel. Adlay starch promoted gluten gel aggregation by strengthening hydrophobic interplay. Adlay starch could interact with gluten in the gel system via hydrogen bonds. Abstract: Effects of adlay starch on the rheological and conformational changes in wheat gluten gel were investigated in this study. Rheological measurement showed that adlay starch-gluten composite gels exhibited higher storage modulus G′ and loss modulus G″ compared with pure gluten gels. This result was also confirmed through morphological analysis. As the addition of adlay starch increased from 0% to 40%, the surface hydrophobicity of gluten protein gel decreased from 16, 660 to 11, 931 and the free thiol content increased from 3.11 to 4.30 µmol/g. In addition, the β-sheet structure in the gluten protein gel increased at the expense of the α-helical structure with increasing adlay starch fraction. This study revealed that besides acting as an inert filler, adlay starch could participate in hydrogen bonding and induce the enhancement of hydrophobic interaction to modify gluten protein association, altering the rheological and structural properties of gluten protein gels.